A High‐Fat Diet Rich in Saturated and Mono‐Unsaturated Fatty Acids Induces Disturbance of Thyroid Lipid Profile and Hypothyroxinemia in Male Rats. Issue 6 (28th February 2018) - Zhang, Xiaohan; Chen, Wenbin; Shao, Shanshan; Xu, Guowang; Song, Yongfeng; Xu, Chao; Gao, Ling; Hu, Chunxiu; Zhao, Jiajun
Abstract : Scope: Increasing evidence has shown that the disturbance of lipid metabolism might make a possible contribution to the pathogenesis of organ dysfunction, including thyroid, yet it is unknown whether excess intake of dietary fat interferes in thyroid lipid profile. We investigate the effects of dietary fat toward the thyroid lipid profile and thyroid function. Methods and results: Male Sprague–Dawley rats are fed with high‐fat diet (HFD) rich in saturated and mono‐unsaturated fatty acids or chow diet for 18 weeks. LC–MS analysis of thyroid shows that total free fatty acids (FFAs) content is significantly higher in HFD rats. The concentration of highly saturated triglycerides significantly increases in HFD rats, whereas the polyunsaturated triglyceride significantly decreases, indicating the decrease in unsaturation in the HFD group. Significant increase of lysophosphatidylcholines (LPC) is observed in HFD rats. Thyroid function tests show hypothyroxinemia (total thyroxine [TT4 ] and free thyroxine [FT4 ]) in HFD rats, and elevated thyrotropin (TSH) concentration. The HFD rats also show decreased thyroid uptake of iodine. Conclusion: Excess intake of dietary fat induces disturbance of thyroid lipid profile and hypothyroxinemia, indicating thyroid dysfunction. We speculate that it may provide a new prospect in understanding the pathogenesis of hypothyroidism. Abstract : Male SD rats were fed with a high‐fat diet (HFD) rich in saturated and mono‐unsaturated fatty acids or chow diet for 18 weeks. LC‐MS analysis of thyroid glands show that HFD interfered with the concentration of FFAs, the composition of fatty acids in triglycerides (TGs), and some other lipid molecules. HFD rats also show hypothyroxinemia, decreased iodine uptake, and downregulation of hepatic T3 ‐responsive genes.